Development of New Methods for Synthesizing Reactive Nanostructured Vanadium Phosphate Catalysts for Partial Oxidation of N-Butane to Maleic Anhydride - Rownaghi, Ali Asghar (2007)
Vanadium phosphate catalysts are well known as the active phase and are commercially used for the selective oxidation of n-butane to maleic anhydride. They represent the sole example of a commercialized material for the catalytic oxidation of an alkane. In this study, vanadium phosphate catalysts were synthesised via three methods including two new methods i.e. new organic and solvothermal method and via dihydrate method. These catalysts were modified by microwave irradiation, addition of dopants and reducing agent. The effect of reducing agents (i.e. isobutyl alcohol, 1-butanol and ethylene glycol), distilled water, microwave irradiation and conventional heating were investigated. Both heating methods gave similar XRD patterns, however microwave irradiated sample showed higher crystallinity which indicated by the high intensity of the peaks. The microwave treated catalysts exhibit a more homogeneous distribution of the rosette- shape surface species and thin structure which consequently enhanced the specific surface area. However, microwave irradiation and the used of water treatment to enhance the crystalline phase, morphology and also increased the total amount of the oxygen species removed. The introduction of Nb, La and Ce as dopants to (VO)2P2O7 catalysts prepared via reduction of VOPO4·2H2O gives significantly increased the surface area and subsequently improved the conversion efficiency of the catalyst. A new organic route for preparation of high surface area (>50 m2g-1) of vanadium phosphate catalyst was developed, by reducing the time from 26 to only 8 h. This together with incorporation of dopants such as Nb, La, and Ce can increase the surface area by reducing the particle size to nanoparticle. The high surface area contributed to higher mobility and better activity of the lattice oxygen and enhanced the conversion and selectivity for achieve a significant yield of maleic anhydride. The new organic route also increased the amount of V5+ phase in the catalyst. An appropriate amount of V5+ phase presence significantly enhanced the activity of VPO catalysts. A novel solvothermal method was also developed by using a number of primary alcohols (C3-C10) at various temperatures (<423 K, 72 h) via a mild solvothermal synthesis to prepare phase-pure crystalline (VO)2P2O7 with specific surface area up to three fold higher than that can be achieved by hydrothermal method. Furthermore, (VO)2P2O7 solid solution can be crystallized in alcohols at temperature lower than that required by hydrothermal conversion. The intensity of (020) phase of nanocrystalline VPO catalyst prepared by the solvothermal were remarkably higher than the hydrothermal method. Another advantage of this new method for the synthesis of the solid solution of vanadium phosphate catalyst is the low consumption of organic media in a close autoclave system. This eliminates the usage of water and yielded higher n-butane conversion catalyst as compared to conventional organic VPO method.